Natural resources and development in Sub-Saharan Africa: Zambia after the privatization of mines - Aguirre-Unceta, Rafael (Iberoamerican Journal of Development Studies, 2016)
An extensive academic literature has been produced for the last twenty-five years on the socalled «natural resource curse» that presumes negative economic and political consequences of the exploitation of such type of resource, in particular in less developed countries. Other authors have come up with policy proposals to counteract these adverse effects and get a beneficial impact from the resource in countries, as the African ones, that don’t have many other options to reinforce the public financial capacity and promote development. Nevertheless, it is not easy to implement these normative policy proposals in the context of weak institutions. At this regard, the article examines the evolution and the policies followed in a poor African country with mining resources (Zambia), especially after the privatization of the extractive industry at the end of the past century.